The Representation of Indigenous Woman in La luna de la hierba roja (José León Sánchez) - Vargas Vargas, José Ángel (2023)
This article analyzes the novel La luna de la hierba roja (1984) by Costa Rican writer José León Sánchez. The main objective is to identify how indigenous women are represented in this novel and its contribution to Costa Rican literature.